Vegetation analysis in Gembes spring area, Ngrayun, Ponorogo regency - Ma’rufah, Amirul; Kusuma Dewi , Nurul; Sulistyarsi, Ani (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Vegetation plays a vital role in water conversion, and one location that provides clean water is a spring. A spring is a location where water emerges from the ground surface. This study aims to collect data on vegetation around Gembes Spring. This type of research is quantitative, using a census research method for tree vegetation and a quadrat plot for understory vegetation. The population used in this research consists of all plants that comprise the vegetation in the spring area. The required samples are plant species found in the observation plot and those identified through direct observation of the trees. Research results have shown a very high level of diversity. The understory vegetation species that dominate the spring area are herbaceous growth forms, while the tree vegetation is dominated by the species Syzygium densiflorum. In conclusion, Zingiber spectabile. The species has the highest INP, followed by Ageratina riparia, which has the second-highest INP, and Globba marantina, with the third-highest INP among all the plant species that make up the understory vegetation.